Allogeneic Hematopoietic Stem Cell Transplantation After Prior Lung Transplantation for Hereditary Pulmonary Alveolar Proteinosis: A Case Report - Beeckmans, Hanne; Ambrocio, Gene P. L.; Bos, Saskia; Vermaut, Astrid; Geudens, Vincent; Vanstapel, Arno; Vanaudenaerde, Bart M.; De Baets, Frans; Malfait, Thomas L. A.; Emonds, Marie-Paule; Van Raemdonck, Dirk E.; Schoemans, Hélène M.; et al. (Frontiers in Immunology, 2022)
Pulmonary alveolar proteinosis (PAP) is a rare, diffuse lung disorder characterized by accumulation of amorphous lipoproteinaceous material (surfactant) in the small airways, due to defective clearance by alveolar macrophages, resulting in impaired gas exchange. Whole lung lavage is the current standard of care treatment for PAP. Lung transplantation is an accepted treatment option in case whole lung lavage or other experimental treatment options are ineffective, or in case of extensive pulmonary fibrosis secondary to PAP. A disadvantage of lung transplantation is recurrence of PAP in the transplanted lungs, especially in hereditary PAP. The hereditary form of PAP is caused by genetic mutations in genes encoding for the granulocyte macrophage-colony stimulating factor (GM-CSF) receptor, and intrinsically affects bone marrow derived-monocytes, which differentiate into macrophages in the lung. Consequently, these macrophages typically display disrupted GM-CSF receptor-signaling, causing defective surfactant clearance. Bone marrow/hematopoietic stem cell transplantation may potentially reverse the lung disease in hereditary PAP. In patients with hereditary PAP undergoing lung transplantation, post-lung transplant recurrence of PAP may theoretically be averted by subsequent hematopoietic stem cell transplantation, which results in a graft-versus-disease (PAP) effect, and thus could improve long-term outcome. We describe the successful long-term post-transplant outcome of a unique case of end-stage respiratory failure due to hereditary PAP-induced pulmonary fibrosis, successfully treated by bilateral lung transplantation and subsequent allogeneic hematopoietic stem cell transplantation. Our report supports treatment with serial lung and hematopoietic stem cell transplantation to improve quality of life and prolong survival, without PAP recurrence, in selected patients with end-stage hereditary PAP.